SOX9 controls epithelial branching by activating RET effector genes during kidney development. - Sock, Elisabeth; Wegner, Michael; et al. (Human Molecular Genetics, 2011)
Congenital abnormalities of the kidney and urinary tract are some of the most common defects detected in the unborn child. Kidney growth is controlled by the GDNF/RET signalling pathway, but the molecular events required for the activation of RET downstream targets are still poorly understood. Here we show that SOX9, a gene involved in campomelic dysplasia (CD) in humans, together with its close homologue SOX8, plays an essential role in RET signalling. Expression of SOX9 can be found from the earliest stages of renal development within the ureteric tip, the ureter mesenchyme and in a segment-specific manner during nephrogenesis. Using a tissue-specific knockout approach, we show that, in the ureteric tip, SOX8 and SOX9 are required for ureter branching, and double-knockout mutants exhibit severe kidney defects ranging from hypoplastic kidneys to renal agenesis. Further genetic analysis shows that SOX8/9 are required downstream of GDNF signalling for the activation of RET effector genes such as Sprouty1 and Etv5. At later stages of development, SOX9 is required to maintain ureteric tip identity and SOX9 ablation induces ectopic nephron formation. Taken together, our study shows that SOX9 acts at multiple steps during kidney organogenesis and identifies SOX8 and SOX9 as key factors within the RET signalling pathway. Our results also explain the aetiology of kidney hypoplasia found in a proportion of CD patients. © The Author 2011. Published by Oxford University Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.med.IB.LPCIPDBI.sox9co